User involvement in digital systems design: Case studies of mobile money innovation in Kenya. Issue 5 (2nd May 2021) - Ongwae, Juliet; Duncombe, Richard
Abstract: This research explores the design of mobile money value‐added services in Kenya that engage marginalized users during the design process. Building on past research that sets out principles for user centered design (UCD), and drawing upon evidence from three case studies, the research finds that system designers follow UCD principles, but decisions to involve users are largely born out of pragmatism, to increase the probability of acceptance of the system, whereas the users main concern were the associated costs, and there was (at least in the early stages) resistance to involvement. This resistance was borne out of a tension between the motivation of the system designers (which was largely non‐altruistic) and the motivation of the users who became involved in the projects through self‐interest or some coercion. The research concludes that system designers require greater appreciation of diversity in interests, asymmetric power and cross‐cultural differences when applying UCD methods. The research extends current knowledge with regard to design interventions in the development of mobile money applications in sub‐Saharan Africa and the recommendations formulated from this research provide practitioners with actionable knowledge to reflect on their current tools and techniques to ensure better localized design processes.